2013
DOI: 10.1155/2013/675391
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Versatile Biological Properties

Abstract: Antimicrobial peptides are diverse group of biologically active molecules with multidimensional properties. In recent past, a wide variety of AMPs with diverse structures have been reported from different sources such as plants, animals, mammals, and microorganisms. The presence of unusual amino acids and structural motifs in AMPs confers unique structural properties to the peptide that attribute for their specific mode of action. The ability of these active AMPs to act as multifunctional effector molecules su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
171
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(179 citation statements)
references
References 142 publications
1
171
0
7
Order By: Relevance
“…Presumably, IB-367 is absorbed to the membrane surface, being incorporated in the hydrophobic core in a transmembrane orientation and forming peptide dimers. 39 The latter oligomerize to form water-filled transmembrane pores, which is reflected by unrestricted transport of ions. 39 The enhanced permeability of cytoplasmic membrane facilitates influx of antibiotics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, IB-367 is absorbed to the membrane surface, being incorporated in the hydrophobic core in a transmembrane orientation and forming peptide dimers. 39 The latter oligomerize to form water-filled transmembrane pores, which is reflected by unrestricted transport of ions. 39 The enhanced permeability of cytoplasmic membrane facilitates influx of antibiotics.…”
mentioning
confidence: 99%
“…39 The latter oligomerize to form water-filled transmembrane pores, which is reflected by unrestricted transport of ions. 39 The enhanced permeability of cytoplasmic membrane facilitates influx of antibiotics. Perhaps, the synergy may also result from disintegration of bacterial membranes by IB-367 and resultant better access of fusidic acid and co-trimoxazole to their intracellular targets, i.e.…”
mentioning
confidence: 99%
“…Most of the naturally occurring AMPs are not optimized for efficient activity and need to be improved through various strategies, before it would be used as therapeutics. Recently, different methods have been tested using the native templates to generate more efficient AMPs such as quantitative structure-activity relationship (QSAR), random mutagenesis, altering the peptide structures by cyclization, or increasing the charge or hydrophobicity of the peptide by tagging 65 . The study revealed that cationicity alone is not the determining factor in the microbicidal activity of antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs can be considered as a promising and potential drug candidate in near future for combating infections and microbial drug resistance, due to their broad range of activity, lesser toxicity and projected slow emergence of resistance development by microbes. Further, their ability to overcome most antibiotic resistance by MDR/XDR strains has also gained considerable attention and clinical interest [9]. Besides antimicrobial functions, AMPs also has ability to act as multifunctional effector molecules such as signaling molecule, immune modulators, mitogen, antitumor, and contraceptive agent that added benefits to explore every aspect of their structural and biological properties for prophylactic and therapeutic applications [10].…”
mentioning
confidence: 99%